Application of bentonite in cement-based composites: A review of current status, challenges and future prospects - Hasan, Kamrul; Putra Jaya, Ramadhansyah; Fadzil, Mat Yahaya (Elsevier Ltd, 2024)
The demand for massive cement production requires vast raw materials, consumes high energy, incurs high costs, and contributes to generating 8–10 % of carbon dioxide (CO2) emissions, which causes enormous ecological and health threats. These issues can be mitigated by adopting sustainable practices, such as using eco-friendly materials in cement production, which is more important than ever. Bentonite (BT), an environmentally friendly alternative, has been widely used as a substitute for cement due to its advantageous properties, including cost reduction, lessened emissions, decreased permeability, and increased chemical resistance. Many researchers have explored the utilization of BT as a substitute for cement in cement-based materials (CBMs) production, however, a comprehensive review substantiating its efficacy in this regard remains to be established. This paper presents a robust literature review and bibliometric analysis conducted on BT, utilizing the VOSviewer tool to scrutinize academic publications. Furthermore, physical and chemical properties, morphological analysis, and the effect of incorporating BT on the fresh, mechanical, and durability properties of CBMs were reviewed. On top of that, BT's life-cycle assessment (LCA) regarding CO2 emissions and overall costs, challenges, opportunities, and future directions were explored, providing valuable insights for researchers and practitioners in the construction field. The literature review of previous studies concluded that incorporating finely ground BT in optimal amounts (10–15 %) could effectively replace cement in concrete production without compromising strength, performance, or durability. Utilizing BT aligns with sustainability goals, offering a promising solution to global ecological challenges and paving the way for a more sustainable future.